Rational choice theory – limitations and alternatives - Krstić, Miloš S (Sociološki pregled, 2020)
In the focus of the paper there are some basic insights and ideas of rational choice theory, that is the “core” of contemporary economic theory. Also, rational choice theory is the “center” of modern political science and is used in various other scientific disciplines, such as: sociology, philosophy, political science, psychology and the like. There are two main goals of this paper. One is to point out the limitations of rational choice theory as one of the theories of economic behavior (and decision making). The second goal is to analyze psychological programs of research of heuristics and bias in behavioral economics and to consider the importance of alternative concepts, models and theories from the point of view of improving the understanding of economic and social behavior.